Intrinsic Element Analysis of Novel: The Forbidden Heaven by Leyla Hana: Analisis Unsur Intrinsik Novel: Surga Terlarang oleh Leyla Hana - Safitri Said; Ibnu Rawandhy N. Hula (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
This study analyzes the intrinsic elements of a novel that is widely read by the Indonesian people because it contains Teenlit and Chicklit simultaneously. This research uses a type of literature study research. Data collection was carried out by the method of documentation from primary sources in the form of a novel entitled "The Forbidden Heaven". The data were analyzed by reading, recording, classifying, and analyzing the seven intrinsic elements. The results of this study show that; 1) The theme of the novel is quite interesting, and strongly inspiring with contradictory diction. 2) Characterization involves sixteen roles, consisting of the main character and auxiliary with the role of the protagonist and tritagonist. 3) The setting of setting presents several places in Jakarta, Bogor, Kuala Lumpur, and Palestine, but is more dominated by Betawi culture, campuses, and proselytizing organizations. 4) The plot presents a story of togetherness that results in love between Najma and Faisal, is separated by studies and eventually proposed by the one who is also the older brother. 5) The style of the novel language is more dominated by the language of the parable the diction used although less touching, but the reader can feel the emotions built with the spiritual narrative of ruhani. 6) Point of view, the author presents various events with a single and second-person first-person point of view, a singular and plural first-person point of view, as well as a mixture. 7) The main mandate of the novel includes three things, namely; a) Intelligent understanding between qadar and taqdir, through mujahadah, endeavor, prayer, and taqarrub because a soul mate is a difficult thing to predict and part of His (Allah) provisions, b) Keep learning and studying wherever and whenever the breath is still blowing, c) Being an inspirational human being, benefiting others, equip themselves for a more eternal hereafter.